Visual fields and foraging ecology of Blacksmith Lapwings Vanellus armatus. (4th April 2019) - Cantlay, Jennifer C.; Portugal, Steven J.; Martin, Graham R.
Abstract : The visual fields of Blacksmith Lapwings Vanellus armatus show the characteristics of visual guided foragers that use precision pecking for prey capture – a binocular field of narrow width and limited vertical extent, with the projection of the bill close to its centre and a large blind area above and behind the head. The topography of the total field, particularly the binocular field, is similar to that of European Golden Plovers Pluvialis apricaria . We suggest that the 'foot‐trembling' behaviour associated with foraging in Plovers is not under visual guidance but forces the escape of hidden prey, which is detected when the prey item moves into the binocular field to enable its capture in the bill. Foot‐trembling thus functions to extend the effective foraging area of a bird beyond the limits of its visual field.